Diagnostic efficacy and suitability of trans-thoracic ultrasonography for pleural fluid detection – The future non-invasive gold-standard? - Irfan, Muhammad; Qureshi, Abdul Rasheed; Ashraf, Zeeshan; Ramzan, Muhammad Amjad; Naeem, Tehmina; Bilal, Huma (Journal of Fatima Jinnah Medical University, 2020)
ABSTRACT Background: Conventionally Pleural effusions are suspected by history of pleuritis, evaluated by physical signs and multiple view radiography. Trans-thoracic pleural aspiration is done and aspirated pleural fluid is considered the gold-standard for pleural effusion. Chest sonography has the advantage of having high diagnostic efficacy over radiography for the detection of pleural effusion. Furthermore, ultrasonography is free from radiation hazards, inexpensive, readily available and feasible for use in ICU, pregnant and pediatric patients. This study aims to explore the diagnostic accuracy of trans-thoracic ultrasonography for pleural fluid detection, which is free of such disadvantages. The objective is to determine the diagnostic efficacy of trans-thoracic ultrasound for detecting pleural effusion and also to assess its suitability for being a non-invasive gold-standard. Subject and Methods: This retrospective study of 4597 cases was conducted at pulmonology OPD-Gulab Devi Teaching Hospital, Lahore from November 2016 to July 2018. Adult patients with clinical features suggesting pleural effusions were included while those where no suspicion of pleural effusion, patients < 14 years and pregnant ladies were excluded. Patients were subjected to chest x-ray PA and Lateral views and chest ultrasonography was done by a senior qualified radiologist in OPD. Ultrasound-guided pleural aspiration was done in OPD & fluid was sent for analysis. At least 10ml aspirated fluid was considered as diagnostic for pleural effusion. Patient files containing history, physical examination, x-ray reports, ultrasound reports, pleural aspiration notes and informed consent were retrieved, reviewed and findings were recorded in the preformed proforma. Results were tabulated and conclusion was drawn by statistical analysis. Results: Out of 4597 cases, 4498 pleural effusion were manifested on CXR and only 2547(56.62%) pleural effusions were proved by ultrasound while 2050 (45.57%) cases were reported as no Pleural effusion. Chest sonography demonstrated sensitivity, specificity, PPV, NPV and diagnostic accuracy 100 % each. Conclusions: Trans-thoracic ultrasonography revealed an excellent efficacy that is why it can be considered as non-invasive gold standard for the detection of pleural effusion.